Inverted and impacted supernumerary tooth: Case report - Subraj Shetty; Treville Pereira (Wolters Kluwer Medknow Publications, 2016)
Inverted teeth have been reported in both maxilla and mandible and mostly they are inverted and impacted third molars and premolars. However, a few cases of inverted supernumerary teeth attached to an impacted third molar have been reported. This case report would add to the academic literature and case series on inverted and impacted teeth. The present case reports an inverted and impacted supernumerary tooth attached to a third molar in a middle-aged male patient.